Access to health services for chronic disease care during the COVID-19 pandemic in Ecuador: A qualitative analysis using a Social Determinants of Health approach - Marta Puig-García; María Fernanda Rivadeneira; Andrés Peralta; Elisa Chilet-Rosell; Ikram Benazizi-Dahbi; María Hernández-Enríquez; Ana Lucía Torres-Castillo; Cintia Caicedo-Montaño; Lucy Anne Parker (Taylor & Francis Group, 2023)
This qualitative study aims to explore how the COVID-19 pandemic impacted healthcare access for patients with chronic conditions in Ecuador from the patient's perspective. We interviewed 19 patients diagnosed with arterial hypertension or type 2 diabetes in rural and urban areas of Ecuador during August and September 2020. We used the Framework Method to analyse the interview transcripts with ATLAS.Ti 8.4 and organised the ideas discussed using categories from the World Health Organization Commission on the Social Determinants of Health conceptual framework. Reorganization of health services during the pandemic meant that patients with arterial hypertension or diabetes could no longer attend face-to-face appointments for disease follow-up. System failures related to medication supply led to increased out-of-pocket payments, which, together with reduced or absent earnings, and in a context with limited social protection policies, meant that patients frequently went for prolonged periods without medication. Rural health initiatives, support from family and use of traditional medicine were reported as ways to manage their chronic condition during this time. Barriers to disease management disproportionately affected individuals with low socioeconomic positions. Stock shortages, lack of protective labour policies and limited reach of anticipatory policies for health emergencies likely worsened pre-existing health inequities in Ecuador.